ANALISI MOTIF DAN SIMBOL SARUNG ADAT TENUN (SENG BULU) KECAMATAN PANTAR TENGAH KABUPATEN ALOR - Gladys Itunde; Evi Fania Panduwal, Fenti Enggerita Kuang, Gabriel Malailak, Fredrik Maata, Halena Muna Bekata, Petr (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
This research aims to explore the symbolic and social meanings of seng bulu woven fabric used by the community in Pantar Tengah Sub-district, Alor Regency, as part of a rich cultural heritage. Through interviews with craftsmen and direct observation of the fabric-making process, this research reveals that seng bulu fabric not only functions as traditional clothing, but also has a deep symbolic value in the social life of the local community. The fabric is used in various traditional ceremonies, such as weddings and deaths, as well as being a symbol of social status that reflects a close relationship with nature and the community. The motifs found on the seng bulu cloth, such as the large flower motif (nanas Mai) and the small flower motif (nasi laki), have meanings associated with abundance, fertility, harmony and togetherness. In addition, colours such as red and black in this fabric contain symbols of courage, strength, and respect for ancestors. The process of making seng bulu cloth, which involves complex stages from yarn selection to weaving, demonstrates traditional skills and knowledge passed down through generations. The results of this study confirm that seng bulu cloth is not just a textile, but a symbol of cultural identity that continues to be valued and preserved by the people of Pantar.